1985
DOI: 10.2307/1309989
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Trophic Interactions and Lake Productivity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and American Institute of BiologicalSciences are collaborating with JSTOR to digitize, preserve and extend access to BioScience. Limnologists ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,316
2
16

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,227 publications
(1,373 citation statements)
references
References 44 publications
39
1,316
2
16
Order By: Relevance
“…Predators often have profound impacts on prey populations and on the organization and function of communities in general (Paine, 1966;Carpenter et al, 1985;Schmitz et al, 1997;Schmitz, 1998;Menge, 2000). The overall effect of predators on communities is determined by interactions between individual predators and prey (Lima, 1998(Lima, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Predators often have profound impacts on prey populations and on the organization and function of communities in general (Paine, 1966;Carpenter et al, 1985;Schmitz et al, 1997;Schmitz, 1998;Menge, 2000). The overall effect of predators on communities is determined by interactions between individual predators and prey (Lima, 1998(Lima, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of regulations changes in Canadarago Lake in 1988 had the potential to cause major changes in the fish population. Major changes in predator populations have been shown to affect entire lake communities [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This model was modified by Oksanen et al (1981) who suggested that productivity determined the number of trophic levels in an ecosystem and that biomass and production in a given trophic level were determined by the higher trophic levels. Such characteristic effects were called 'cascading' effects (Carpenter et al, 1985). Persson et al (1988) used this model to integrate bottom-up and top-down effects.…”
Section: Edibility Of Phytoplanktonmentioning
confidence: 99%